Gray's atlas of anatomy - Drake, Richard L.; Vogl, A. Wayne; Mitchell, Adam W.M. (Philadelphia : Elsevier, 2021)
'Clinically focused, consistently and clearly illustrated, and logically organized, Gray's Atlas of Anatomy, the companion resource to the popular Gray's Anatomy for Students, presents a vivid, visual depiction of anatomical structures. Stunning illustrations demonstrate the correlation of structures with clinical images and surface anatomy - essential for proper identification in the dissection lab and successful preparation for course exams'--
Includes index.
This book includes online access at https://ebooks.health.elsevier.com/login, please refer library staff for the password.
Keywords: Anatomy; Atlases